2010
DOI: 10.5005/jp-journals-10009-1166
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Transcerebellar Diameter to Abdominal Circumference Ratio (TCD/AC) in the Assessment of Normal Fetal Growth

Abstract: Objective To derive population specific transverse cerebellar diameter/abdominal circumference ratio (TCD/AC ratio) for the assessment of normal fetal growth. Materials and methods A one-year prospective observational study conducted at the KLE University's teaching hospital, Belgaum. The TCD/AC ratio was calculated for 434 obstetric patients, who met the inclusion criteria and the arithmetic mean and 1 standard deviation (SD) was calculated for the population studied. Results Within the study population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(23 reference statements)
2
5
0
Order By: Relevance
“…23 Dhumale et al have also assessed normal fetal growth with TCD/AC ratio and gestational ratio ranging from 18 to 34 weeks and found to be constant with a mean of 13.56±1.21 (SD). 24 The study findings was found to be consistent with the findings of the Meyer et al 25 On comparing various parameters of HC/AC in diagnosing asymmetrical IUGR with various studies like Belizan et al showed elevated cut off values with 82% sensitivity, 94% specificity, 62% positive predictive value and 98% negative predictive value. 26 The study findings of PPV was found to be contradictory with the findings of Divon et al, Meyer et al and Kurjak et al with positive predictive values of 67%, 75.6% and 80% respectively.…”
Section: Apgar Scoresupporting
confidence: 86%
“…23 Dhumale et al have also assessed normal fetal growth with TCD/AC ratio and gestational ratio ranging from 18 to 34 weeks and found to be constant with a mean of 13.56±1.21 (SD). 24 The study findings was found to be consistent with the findings of the Meyer et al 25 On comparing various parameters of HC/AC in diagnosing asymmetrical IUGR with various studies like Belizan et al showed elevated cut off values with 82% sensitivity, 94% specificity, 62% positive predictive value and 98% negative predictive value. 26 The study findings of PPV was found to be contradictory with the findings of Divon et al, Meyer et al and Kurjak et al with positive predictive values of 67%, 75.6% and 80% respectively.…”
Section: Apgar Scoresupporting
confidence: 86%
“…These results are consistent with the regression results, where the AUC was also low. Comparing the diagnostic value of previous and current cutoff data, the significance is inconclusive and difficult to compare with other studies due to smaller case numbers and different cutoff values [15,17,26,[33][34][35]. The diverse populations studied could explain the variance between TCD/AC ratios, resulting in differing cutoff values.…”
Section: Discussionmentioning
confidence: 88%
“…TCD/AC ratio: In theory, the TCD/AC-ratio is a perfect parameter for the detection of FGR, as chronic fetal hypoxia affects the TCD less than other biometric parameters and the AC is a more sensitive parameter for fetal growth than BPD or FL. This is particularly the case in fetuses of uncertain gestational age, as the TCD/AC ratio remained relatively constant throughout gestation [ 13 , 14 , 17 , 33 , 34 ]. In a prospective study of 825 low-risk pregnancies and 158 pregnancies at risk of growth retardation, Meyer et al demonstrated that the TCD/AC ratio has a high sensitivity (83.9%) for SGA and noted that the TCD/AC ratio is an accurate, gestational-age-independent method of identifying SGA infants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated good correlation between TCD and AC [8]. Many studies have shown that TCD/AC ratio is a stable, gestational age independent parameter after 20 weeks of gestation [9,10]. Increased TCD/AC values are suspicious of fetal growth restriction [3,11] and may be useful in the early detection of fetal IUGR.…”
Section: Discussionmentioning
confidence: 99%